Fenologia, produtividade e caracterização físico-química de frutos de Myrsine coriacea (Sw.) R. Br. Ex Roem & Schult. (capororoca) e Cecropia pachystachya Trec. (embaúba) - Putini, Francisco Alberto (2013)
Given the environmental and economic importance of tropical forests, there is a need to reconcile the environmental, social and economical through sustainable management. In Brazil, there are a large number of forest species that have shown good sources of nutrients and require research to meet the demands of the food industry, pharmaceutical and cosmetics industries. This study aimed to contribute to the understanding of phenology, productivity and physicochemical characteristics of fruits of two species, to provide input to management actions of non-timber forest products in forest remnants. The two dioecious species, Myrsine coriacea (Sw.) R. Br Ex Roem & Schult. (Capororoca) and Cecropia pachystachya Trec. (Embaúba), were chosen for the abundance in the coastal plain of the Paraná and the market potential for fruit. The study was conducted in Salto Morato Natural Reserve, Guaraqueçaba -PR. The study of phenology approached the male and female in both species. Capororoca showed occurrence of ripe fruit in two seasons and a negative correlation between the prefruiting and temperature. Embaúba showed no correlation between seasonality or phenophases and climatic variables. In relation to fruit yield, we assessed the number and weight of fruits, 1,012,045 fruits and 22.9 kg resulted to Capororoca, 426 infrutescences with 15.9 kg to Embaúba. For physicochemical characterization were evaluated dimensions of fruit, fresh and dry weight, soluble solids, pH and titratable acidity. The results showed that Capororoca shows the fresh weight of fruit is 20%, 4.94ºbrix and a pH of 4.96 in average, while Embaúba also presents 20% of weight, and 4.46 º brix pH 4.95 on average. The phenology and productivity indicate that it is possible to plan the production of these fruits in forest remains, however, as indicated by the physico-chemical characterization, it is necessary to implement a program of selection and breeding to standardize the fruits and meet market demands